Slipper orchids in art and scienc - Cribb, Phillip (Lankesteriana: International Journal on Orchidology, 2014)
The lady’s slippers, orchids with showy and unusual flowers with considerable diversity in shape, size and colour, are amongst the most popular of all orchids in science and horticulture. Consequently, the botanical and horticultural literature on them is extensive. Artists and designers have also been intrigued by them and they feature in many illustrated botanical and horticultural books and decorative items, from tapestries to porcelain and stamps. In this article, the history of slipper orchids is illustrated by reference to illustrations of them, mostly in the collections of the Royal Botanic Gardens. Kew.